Management of rare inherited bleeding disorders: Proposals of the French Reference Centre on Haemophilia and Rare Coagulation Disorders. (20th February 2023) - Trossaert, Marc; Chamouard, Valerie; Biron‐Andreani, Christine; Casini, Alessandro; De Mazancourt, Philippe; De Raucourt, Emmanuelle; Drillaud, Nicolas; Frotscher, Birgit; Guillet, Benoit; Lebreton, Aurelien; Roussel‐Robert, Valerie; Rugeri, Lucia; et al.
Abstract: Introduction: The rare coagulation disorders may present significant difficulties in diagnosis and management. In addition, considerable inter‐individual variation in bleeding phenotype is observed amongst affected individuals, making the bleeding risk difficult to assess in affected individuals. The last international recommendations on rare inherited bleeding disorders (RIBDs) were published by the United Kingdom Haemophilia Centre Doctors' Organisation in 2014. Since then, new drugs have been marketed, news studies on surgery management in patients with RIBD have been published, and new orphan diseases have been described. Aim: Therefore, the two main objectives of this review, based on the recent recommendations published by the French Reference Centre on Haemophilia and Rare Bleeding Disorders, are: (i) to briefly describe RIBD (clinical presentation and diagnostic work‐up) to help physicians in patient screening for the early detection of such disorders; and (ii) to focus on the current management of acute haemorrhages and long term prophylaxis, surgical interventions, and pregnancy/delivery in patients with RIBD.